The study of conceptual metaphors in ESAP L2 writing: range and variability - Permyakova, Tatiana; Utkina, Tatiana (Research in Language, 2016)
The article presents the study of the influence of professional competence of EFL learners on their academic writing. The task was approached through analyzing learners’ competence in specific knowledge domains - knowledge of terms and specific concepts, represented as conceptual metaphors. Conceptual metaphor models were analyzed in the English written texts produced by Russian students with different competences in economics – at both non-professional and professional levels of academic discourse (NPAD and PAD respectively). Metaphor Identification Procedure VU University Amsterdam (MIPVU) was applied to metaphor identification, and alternative metaphor and preferential conceptualization analysis was performed to compare the scope of source and the range of target in NPAD and PAD. Findings highlight the areas of commonality as well as divergence in terms of students’ professional competence represented in conceptual metaphors in L2 writing. The main differences in the scope of the source analysis are quantitative rather than qualitative. The range of target comparison between NPAD and PAD indicates a significantly larger range of targets for the professional level students, a lower level of metaphorization for the non-professional level, and inclusive strategies across the two levels. Practical recommendations suggest an improved research methodology for studying metaphor production in EAP and ESP as well as a deeper understanding of ESP content and its structure.